Electrospun Ceramic Nanofiber Mats Today: Synthesis, Properties, and Applications - Esfahani, Hamid; Ramakrishna, Seeram; Rajan, Jose (MDPI AG, Basel, Switzerland, 2017)
Ceramic nanofibers (NFs) have recently been developed for advanced applications due to their unique properties. In this article, we review developments in electrospun ceramic NFs with regard to their fabrication process, properties, and applications. We find that surface activity of electrospun ceramic NFs is improved by post pyrolysis, hydrothermal, and carbothermal processes. Also, when combined with another surface modification methods, electrospun ceramic NFs result in the advancement of properties and widening of the application domains. With the decrease in diameter and length of a fiber, many properties of fibrous materials are modified; characteristics of such ceramic NFs are different from their wide and long (bulk) counterparts. In this article, electrospun ceramic NFs are reviewed with an emphasis on their applications as catalysts, membranes, sensors, biomaterials, fuel cells, batteries, supercapacitors, energy harvesting systems, electric and magnetic parts, conductive wires, and wearable electronic textiles. Furthermore, properties of ceramic nanofibers, which enable the above applications, and techniques to characterize them are briefly outlined.